Technology development for ultraintense all-OPCPA systems. (2019) - Bromage, J.; Bahk, S.-W.; Begishev, I. A.; Dorrer, C.; Guardalben, M. J.; Hoffman, B. N.; Oliver, J. B.; Roides, R. G.; Schiesser, E. M.; Shoup III, M. J.; Spilatro, M.; Webb, B.; et al.
Abstract : Optical parametric chirped-pulse amplification (OPCPA) [Dubietis et al., Opt. Commun. 88, 437 (1992)] implemented by multikilojoule Nd:glass pump lasers is a promising approach to produce ultraintense pulses ( ${>}10^{23}~\text{W}/\text{cm}^{2}$ ). Technologies are being developed to upgrade the OMEGA EP Laser System with the goal to pump an optical parametric amplifier line (EP OPAL) with two of the OMEGA EP beamlines. The resulting ultraintense pulses (1.5 kJ, 20 fs, $10^{24}~\text{W}/\text{cm}^{2}$ ) would be used jointly with picosecond and nanosecond pulses produced by the other two beamlines. A midscale OPAL pumped by the Multi-Terawatt (MTW) laser is being constructed to produce 7.5-J, 15-fs pulses and demonstrate scalable technologies suitable for the upgrade. MTW OPAL will share a target area with the MTW laser (50 J, 1 to 100 ps), enabling several joint-shot configurations. We report on the status of the MTW OPAL system, and the technology development required for this class of all-OPCPA laser system for ultraintense pulses.